The vitamin D level in umbilical cord blood in premature infants with or without intra-ventricular hemorrhage: A cross-sectional study - Hassan Boskabadi; Maryam Zakerihamidi; Raheleh Faramarzi (Shahid Sadoughi University of Medical Sciences, 2018)
Background: Intra-ventricular hemorrhage (IVH) is acute cerebral complications of premature infants which may lead to the long-term problems. Objective: According to the role of vitamin D in the stability of the blood vessels, the present study was carried out in order to compare the vitamin D level in the premature infants with or without IVH. Materials and Methods: This cross-sectional study was carried out on 180 premature infants in the Ghaem Hospital, Mashhad, Iran 97 infants without IVH (53.9%) and 83 with IVH (46.1%) through convenience sampling technique in 2015-2017. Serum vitamin D level of funiculus in the two groups was compared. A researcher made questionnaire was used which includes infants’ personal and laboratory information; and their mother's information. Results: Seventy nine percent of infants suffered from vitamin D deficiency in which 33.9% had a severe deficiency (less than 10 ng/ml), 30% moderate deficiency (10.1-20 ng/ml), 15% slight deficiency (20.1-30 ng/ml) and 21.1% had normal vitamin D (>30.1 ng/ml). Vitamin D mean±SD of infants in the control group, 23.71±12.98 ng/ml and case group 15.92±10.27 ng/ml (p<0.001). In total 92.8% of infants with IVH had levels of vitamin D below30 ng/ml, while this rate was 67% in infants without IVH. Conclusion: Vitamin D deficiency in the premature infants is very common. Also, the serum vitamin D level in infants with IVH was less than infants without IVH. Therefore, the recommendation of vitamin D may be effective in the prevention of neonatal IVH.